Bi-Layered, Ultrathin Coating Initiated Relay Response to Impart Superior Fire Resistance for Polymeric and Metallic Substrates - Wei Tang; Qi Chen; Junxiao Li; Xiang Ao; Yunhuan Liu; Lijun Qian; Silvia González Prolongo; Yong Qiu; De-Yi Wang (Nano-Micro Letters)
Highlights Relay response of bi-layered coating achieved fast response and extended protection. 320-µm coating achieved over 900 s of burn-through resistance. 320-µm coating achieved extended electrochemical stability for battery under fire.